Role of tumor necrosis factor alpha in the pathogenesis of atrial fibrillation: A novel potential therapeutic target?. (June 2015) - Ren, Manyi; Li, Xiuzhen; Hao, Li; Zhong, Jingquan
Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia in clinical practice and a major cause of morbidity and mortality. Although the fundamental mechanisms underlying AF remain incompletely understood, atrial remodeling, including structural, electrical, contractile, and autonomic remodeling, has been demonstrated to contribute to the substrate for AF maintenance. Accumulating evidence shows that tumor necrosis factor alpha (TNF-α) plays exceedingly important roles in atrial remodeling. This article reviews recent advances in the roles of TNF-α in the pathogenesis of AF, elucidates the related mechanisms, and exploits its potential usefulness as a novel therapeutic target.